Transcreating Lal Shalu: - Anik Biswas (Crossings, 2022)
Roman Jakobson classifies film adaptation as an “Intersemiotic Translation” (qtd. in Munday 5) and Andre Lefevere sees every translation as “potentially the most influential form of rewriting” (qtd. in Munday 142). Both of the ideas open up a space to think about the relocation of language from the source text to the re-written text and layers of transformation from the text to screen in case of making any film based on a literary text. In Speaking of Films, Satyajit Ray opines: “Just as a writer has words at his disposal, a film-maker has image and sound that make up the language of cinema” (28). Tanvir Mokammel’s film Lal Shalu draws attention significantly as an intersemiotic translation of Syed Walliullah’s Lal Shalu with all its changes and manifestations in cinematic language. There is no specific way of determining how much liberty one filmmaker can enjoy in converting the language of the source text into that of the target text, and it leads to creating room to rethink the parallelism between the language of the source text and the presentation of the “translated text” through image and sound. This paper aims at exploring how transformation takes place in Tanvir Mokammel’s Lal Shalu and its appropriateness as an intersemiotic cinematographic translation.